A clinical study of non-diabetic soft tissue infections: risk factors for mortality and morbidity - Muthusami, Anitha; Krishnaswamy, Jawahar; Sattar, Reshma (International Surgery Journal, 2017)
Background: Non-diabetic soft tissue infection is the infection of the soft tissue in a non-diabetic patient. It is rare, but results in high mortality. The aim of the study was to establish a scoring system to predict the outcome of a patient with non-diabetic soft tissue limb infection at the time of admission and to determine the factors which increase the morbidity of a patient with non-diabetic soft tissue limb infection as determined by number of days of hospital stay or limb loss or death of the patient. Methods: Clinical and laboratory details of 200 cases of non-diabetic soft tissue infections of the lower limb were retrospectively analyzed statistically, using pearson's chi square test for comparison of proportions with respect to mortality, fisher's exact test, logistic regression analysis were expressed using beta coefficient values, odds ratios. Statistical analysis was performed using SPSS software version 12. Results: Two hundred patients records were reviewed. 121 patients (60%) were males and 79 (40%) were females. Mean age was 52.5 years ranging from 14 to 91 years. Forty-six patients underwent conservative treatment, 111 patients underwent debridement and 43 patients underwent amputation. Increasing age were the risk factor associated with mortality in non-diabetic soft tissue infections that were statistically significant. Conclusions: Non-diabetic soft tissue infections still lead to high mortality and morbidity despite the use of appropriate conservative treatment, aggressive debridement, resuscitation and amputation. In this series, there is high mortality associated with increasing age.